2011
DOI: 10.1371/journal.pone.0025304
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Decisions in Human Social Interactions Using Real-Time fMRI and Pattern Classification

Abstract: Negotiation and trade typically require a mutual interaction while simultaneously resting in uncertainty which decision the partner ultimately will make at the end of the process. Assessing already during the negotiation in which direction one's counterpart tends would provide a tremendous advantage. Recently, neuroimaging techniques combined with multivariate pattern classification of the acquired data have made it possible to discriminate subjective states of mind on the basis of their neuronal activation si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 56 publications
1
39
0
1
Order By: Relevance
“…In light of this new view, optimal decoding of faces and places from these regions call for a multivariate decoding approach that can detect these overlapping and distributed neural patterns. Therefore, in this study, we used whole‐brain data to train a classifier to predict the mental state of a subject as this approach does not rely on any prior assumptions about functional localization (Laconte et al ., ; Anderson et al ., ; Hollmann et al ., ; Lee et al ., ; Xi et al ., ; DeBettencourt et al ., ). Moreover, the whole‐brain decoder is highly suited for real‐time fMRI because it automatically identifies sparse and distributed patterns of activity that are representation‐specific.…”
Section: Introductionmentioning
confidence: 98%
“…In light of this new view, optimal decoding of faces and places from these regions call for a multivariate decoding approach that can detect these overlapping and distributed neural patterns. Therefore, in this study, we used whole‐brain data to train a classifier to predict the mental state of a subject as this approach does not rely on any prior assumptions about functional localization (Laconte et al ., ; Anderson et al ., ; Hollmann et al ., ; Lee et al ., ; Xi et al ., ; DeBettencourt et al ., ). Moreover, the whole‐brain decoder is highly suited for real‐time fMRI because it automatically identifies sparse and distributed patterns of activity that are representation‐specific.…”
Section: Introductionmentioning
confidence: 98%
“…These trained pattern classifiers can then predict subsequent manifest cognitive states by reading the evoked neural activation patterns (represented by a spatially distributed set of activated voxels in the context of fMRI), based on the experience gained during training (for review, see Haynes & Rees, 2006). Pattern classifiers have been applied in real-time fMRI paradigms (Hollmann et al, 2011;LaConte, Peltier, & Hu, 2007;Sitaram et al, 2011) and have been shown to improve performance in perceptual discrimination tasks through neurofeedback training (Shibata, Watanabe, Sasaki, & Kawato, 2011). MVPA could potentially be utilized to overcome the limitations of univariate real-time fMRI methods in the context of PD, by avoiding an a priori approach and by closely modeling the complex network dynamics that underpin this pathology.…”
Section: Results and Discussion Of Neurofeedback Trialsmentioning
confidence: 99%
“…A recent study used this technique to demonstrate a 75% accuracy rate on trained words, and about a 60% accuracy on untrained but semantically related words (Mitchell, Shinkareva, Carlson, Chang, Malave, Mason et al, 2008), and another used it to communicate with minimally conscious patients using a yes/no response (Monti, Vanhaudenhuyse, Coleman, Boly, Pickard, Tshibanda et al, 2010). One group of researchers combined pattern classification with real-time analysis to successfully predict decisions in real time during an ultimatum game (Hollmann, Rieger, Baecke, Lützkendorf, Müller, Adolf et al, 2011). As elegant as they are, note that all of these studies either require many exemplars from the same individual or make prediction from one individual to a large group of others (i.e., on average), but none can yield the content of a given thought without at least some prior information.…”
Section: Mind Reading?mentioning
confidence: 99%